The Truth About the Scientific Miracle in the Stages of Human Weakness in the Verse of Surat Yasin - Safia Ali Morshed Mohammad Thah; Yousef Mohammed Abdo Mohammed Al-Awadhy (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
This research seeks to contribute to resolving the problem of the extent to which the meaning of the Almighty's saying:  (وَمَن نُّعَمِّرْهُ نُنَكِّسْهُ فِى ٱلْخَلْقِ ۖ أَفَلَا يَعْقِلُونَ)[Surah Yasin: 68], is consistent with modern scientific discoveries. The research aims to prove the truth of the scientific miracle in the aforementioned verse. The researcher followed the inductive approach in tracing the cosmic verses in Surah Yasin, which discuss the signs of God Almighty in the reversal. The researcher also followed the analytical approach by carefully explaining the intended vocabulary in the Quranic verses, detailing them from a linguistic perspective, and then clarifying their meaning in a comprehensive manner. The researcher also followed the comparative approach by comparing the statements of scholars of medicine, cosmology, and science with the statements of scholars of linguistics and exegesis. To arrive at the truth of the miracle, the research has reached a number of conclusions, the most important of which are: 1). The stage of decline for those who have reached old age is something that God Almighty has decreed for all of humanity, from which there is no escape. 2). Aging is nothing but a form of programmed death for the body, 3). Aging consists of comprehensive changes affecting all organs of the human body after its maturity and advancement in age, which leads to the loss of many of life's pleasures due to the inability to perform them. 4). People's lives pass through four stages: a). The first stage: childhood and growth, which extends from early life to the age of thirty-three, the peak of youth and maturity, b). The second stage: the age of maturity, which extends from the age of thirty-three to forty, the peak of strength and mental maturity, c). The third stage: middle age, which extends from forty to sixty, the beginning of human imperfection, but it is a subtle imperfection, d). The fourth stage: old age and apparent deterioration. According to doctors, this stage reaches 120 years of age. 5). The Qur'anic verses indicate that the elderly person's state changes from strength to weakness, encompassing both physical and mental change. This is consistent with what modern science has discovered, namely that aging affects all human organs.